Even Semester Students’ Perception on English Language Learning Conducted Online - Erwita, Ika; Lase, Ertaniat; Waruwu, Yaredi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to gain in-depth insight into students' perception on online English learning. In the face of the digital age, online learning has become a major alternative in higher education. However, the understanding of how students assess this learning experience is still evolving. The type of research method used is quantitative research with a data collection model using a questionnaire, which was distributed to students through Google Forms to all participants of this study and the data was analyzed using descriptive statistics to get the percentage of students' perspectives. The results showed that, from the perceptions of students who became participants in this study, felt that online English language learning did not fully help the learning process to be more effective and preferred English language learning conducted face-to-face